PD-1 promotes immune exhaustion by inducing antiviral T cell motility paralysis - Zinselmeyer, Bernd H.; Heydari, Sara; Sacristán, Catarina; Nayak, Debasis; Cammer, Michael; Herz, Jasmin; Cheng, Xiaoxiao; Davis, Simon J.; Dustin, Michael L.; McGavern, Dorian B. (The Journal of experimental medicine, 2013)
Immune responses to persistent viral infections and cancer often fail because of intense regulation of antigen-specific T cells—a process referred to as immune exhaustion. The mechanisms that underlie the induction of exhaustion are not completely understood. To gain novel insights into this process, we simultaneously examined the dynamics of virus-specific CD8+ and CD4+ T cells in the living spleen by two-photon microscopy (TPM) during the establishment of an acute or persistent viral infection. We demonstrate that immune exhaustion during viral persistence maps anatomically to the splenic marginal zone/red pulp and is defined by prolonged motility paralysis of virus-specific CD8+ and CD4+ T cells. Unexpectedly, therapeutic blockade of PD-1–PD-L1 restored CD8+ T cell motility within 30 min, despite the presence of high viral loads. This result was supported by planar bilayer data showing that PD-L1 localizes to the central supramolecular activation cluster, decreases antiviral CD8+ T cell motility, and promotes stable immunological synapse formation. Restoration of T cell motility in vivo was followed by recovery of cell signaling and effector functions, which gave rise to a fatal disease mediated by IFN-γ. We conclude that motility paralysis is a manifestation of immune exhaustion induced by PD-1 that prevents antiviral CD8+ T cells from performing their effector functions and subjects them to prolonged states of negative immune regulation.